Histological analysis and the blood flux in kidneys submitted to different periods of ischemia/reperfusion - Meyer,Fernando (2011)
PURPOSE: Evaluate the renal blood flow by using a laser flow meter, Laserflow Vasamedics®, after the ischemia/reperfusion in two different times of the arterial renal vessel clamping. METHODS: The renal blood flow was evaluated by using a laser flow meter after two different times of ischemia/reperfusion procedure, 30 and 60 minutes. It was used 20 Wistar male rats, divided in two groups of 10 rats: Group A (30 minutes of ischemia on the left kidney, with later analysis of the blood flow in 1, 5 and 20, after the renal reperfusion start) and Group B (60 minutes of ischemia on the left kidney, with later analysis of the blood flow in 1, 5 and 20 minutes, after the renal reperfusion start). RESULTS: In the first minute, there were not significant differences between the two groups (p=0.789). In the 5th minute there were not significant differences also, but there was a tendency (p=0.068). In the 20th minute, there was a significant difference between the 2 groups (p=0.022). When the means are observed, it is possible to notice that Group A has a larger flux than Group B. CONCLUSION: The kidneys submitted to 30' of ischemia/reperfusion are subject to a larger restitution of the blood flow in comparison to the Group which had a longer time.